Burkholderia multivorans requires species‐specific GltJK for entry of a contact‐dependent growth inhibition system protein. Issue 3 (28th July 2021) - Myers‐Morales, Tanya; Sim, Martha M. S.; DuCote, Tanner J.; Garcia, Erin C.
Abstract: Interbacterial antagonism and communication are driving forces behind microbial community development. In many Gram‐negative bacteria, contact‐dependent growth inhibition (CDI) systems contribute to these microbial interactions. CDI systems deliver the toxic C‐terminus of a large surface exposed protein to the cytoplasm of neighboring bacteria upon cell−contact. Termed the BcpA‐CT, import of this toxic effector domain is mediated by specific, yet largely unknown receptors on the recipient cell outer and inner membranes. In this study, we demonstrated that cytoplasmic membrane proteins GltJK, components of a predicted ABC‐type transporter, are required for entry of CDI system protein BcpA‐2 into Burkholderia multivorans recipient cells. Consistent with current CDI models, gltJK were also required for recipient cell susceptibility to a distinct BcpA‐CT that shared sequences within the predicted "translocation domain" of BcpA‐2. Strikingly, this translocation domain showed low sequence identity to the analogous region of an Escherichia coli GltJK‐utilizing CDI system protein. Our results demonstrated that recipient bacteria expressing E. coli gltJK were resistant to BcpA‐2‐mediated interbacterial antagonism, suggesting that BcpA‐2 specifically recognizes Burkholderia GltJK. Using a series of chimeric proteins, the specificity determinant was mapped to Burkholderia ‐specific sequences at the GltK C‐terminus, providing insight into BcpA transport across the recipient cell cytoplasmic membrane. Abstract : Contact‐dependent growth inhibition systems mediate inter‐bacterial antagonism by delivering toxic effectors to neighboring bacteria. This study identifies inner membrane proteins GltJK as a likely receptor for recipient cell import of a Burkholderia multivorans CDI system effector, BcpA‐2. Specificity of the receptor is mapped to the GltK C‐terminus, suggesting that this region plays an important role in the translocation of BcpA‐2 across the recipient bacterium cytoplasmic membrane.